Performance Assessment of Pile Embedded in Expansive Soil - Albusoda, Bushra S.; Al-Anbary, Laith A. (Al-Khwarizmi Engineering Journal, 2016)
An evaluation for the performance of model pile embedded in expansive soil was investigated. An extensive testing program was planned to achieve the purpose of this research. Therefore, special manufactured system was prepared for studying the behavior of model pile having different length to diameter ratios (L/D). Two types of piles were used in this research, straight shaft and under reamed piles. The effect of model pile type, L/D ratio and number of wetting drying cycles were studied. It is observed that significant reductions in pile movement when under reamed piles were considered. A proposed design charts was presented for straight shaft and under reamed piles to estimate the length of both types of piles that is required to exert minimized uplift pressure when the soil swells.